Sacarificação da celulose utilizando carvões funcionalizados - Miranda, Mayara de Souza (2017)
The hydrolysis or saccharification of cellulosic biomass produces glucose (besides other sugars), that undergo to fermentation to obtain a second-generation ethanol. One of the challenges of this assay is to process the hydrolysis into glucose with higher conversion rate of sugars and good yields. In this work, catalysts were prepared from carbonaceous materials, aiming of using them in cellulose hydrolysis reactions. Precursors of the catalysts were carbonized coffee husk (CCC) and commercial activated charcoal (CAC). Both precursors were functionalized by sulfonation process, obtaining CCCS (sulfonated carbonized coffee husk) and CACS (sulfonated commercial activated carbon). The materials were characterized by the following techniques: Scanning Electron Microscopy (SEM), Thermogravimetric analysis (TGA), X-ray Fluorescence (XRF) and Infrared Spectroscopy (FTIR) and Elemental Analysis (CHNS-O). Characterization results of the catalysts indicated that the sulfonation process has been more efficient for the carbon originated from the carbonized coffee husk (CCC) compared to the commercial activated charcoal (CAC). Afterwards, hydrolysis reactions of microcrystalline cellulose (CMC), cellobiose (CB) and sugarcane bagasse (BC) were conducted using the catalysts prepared. To evaluate reaction products, yields of total reducing sugars (% ART) were determined using the DNS method, and the amount of glucose by High Performance Liquid Chromatography (HPLC). In general, higher amounts of glucose were obtained from the hydrolysis of cellobiose using the CCCS catalyst (34338mg/L). Glucose Yield was 24% higher than reference. Higher percentages of ART and glucose were obtained for hydrolysis reactions of microcrystalline cellulose using the CCCS as a catalyst, 15,2% e 20492mg/L respectively, when compared to reactions with sugarcane bagasse. About sugarcane bagasse, the CACS catalyst showed a higher conversion rate to glucose than the other catalyst. Therefore, CCCS catalyst proved to be more efficient in obtaining glucose from cellulose and cellobiose.